107k views
0 votes
Please Please Please find the average rate of change and possibly explain it?

g ( x ) = − 3 x^ 3 + 4 from x = − 2 to x = 1

2 Answers

3 votes
Answer:
9

Step-by-step explanation:
Use the average rate of change equation
g(b)-g(a) / b-a
a = -2 b = 1

g(b) = g(1) = -3(1)^3 + 4 = 1
g(a) = g(-2) = -3(-2)^3 + 4 = 28

(1-28) / (1-(-2))
-27 / 3
-9
User Dspies
by
4.9k points
4 votes

Samia2020 is correct it’s -9

User Masako
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.